Peran Kurikulum Merdeka dalam Meningkatkan Keaktifan Siswa pada Pembelajaran PAK - Agnes Pasaribu; Ordekoria Saragih (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
The Independent Curriculum is an approach to global education created to provide more freedom for teachers and students in the learning process. In the context of Christian Religious Education (PAK), the Independent Curriculum is needed to increase student activity through the implementation of learning that is more flexible and in sync with the needs and potential of each student. This research aims to explore the role of the Merdeka Curriculum in increasing students' activeness in PAK learning. Through a more student-centered approach and encouraging active participation, the Independent Curriculum is needed to create a more enjoyable, creative and productive learning atmosphere. The results of this research show that the application of the Merdeka Curriculum in PAK can increase student activity, both in terms of emotional, intellectual and social involvement. Thus, the Independent Curriculum not only places freedom in learning, but is also the key to creating a progressive and effective learning atmosphere.